Analisis Miskonsepsi dan Pemberian Scaffolding Peserta Didik SMP dalam Menyelesaikan Soal Cryptarithmetic Menggunakan Four–Tier Essay Diagnostic Test - Ningseh, Sinta Agustin; Salsabila, Shefira; Rofiki, Imam (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
One of the learning challenges of junior high school students in solving problems is characterized by misconceptions experienced by students. Moreover, cryptarithmetic as a special material topic related to problem solving. So, efforts to find out the existence of misconceptions while minimizing is to use the Four-Tier Essay Diagnostic Test and scaffolding. Research This study aims to determine the misconceptions and factors that cause misconceptions experienced by students in solving problems. misconceptions and factors causing misconceptions experienced by students in solving cryptarithmetic problems and providing scaffolding. and the provision of scaffolding. The research method used is qualitative approach with descriptive method. This research was conducted at SMP Negeri 19 Malang by selecting 3 subjects who experienced all three types of misconceptions. misconceptions. The instruments used in this research are the Four-Tier Essay Diagnostic Test questions, semi-structured interview guidelines for teachers and students, and teachers and students, and scaffolding guidelines as well as instrument validation sheets. The results showed that the occurrence of classificational misconceptions, correlational misconceptions, and correlational misconceptions. misconceptions, correlational misconceptions, and theoretical misconceptions caused by a lack of understanding of basic concepts, lack of practice problems or experience. basic concepts, lack of practice problems or learning experience, and errors in understanding the problems. in understanding the problem. Therefore, one to one scaffolding was given at level 2 (explaining, receiving, and restructuring) and level 3 (developing conceptual thinking) to each of them. conceptual thinking) for each student. Based on this, it shows that scaffolding can reduce misconceptions in solving cryptarithmetic problems